2015
DOI: 10.1525/as.2015.55.3.548
|View full text |Cite
|
Sign up to set email alerts
|

How Economic, Strategic, and Domestic Factors Shape Patterns of Conflict and Cooperation in the East China Sea Dispute

Abstract: Despite frequent talk of conflict and even war, economic and strategic factors suggest that the Sino–Japanese dispute over the East China Sea will not erupt into hot conflict, at least for the time being. However, for domestic reasons, overt cooperation remains a distant prospect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The islands’ proximity to the Chinese mainland, Taiwan and Japan's southernmost islands ( nansei‐shotō ), has resulted in multiple conflicting claims that they are within all of these territories’ maritime areas, creating a complex maritime dispute. Today, Japan's position holds that the Senkaku Islands are within the 200 nautical miles that are defined as Japan's economic zone (O'Shea, , pp. 551–553) and that "there exists no issue of territorial sovereignty" (MOFA, , p. 2).…”
Section: The Senkaku Islands Dispute—territorial and Maritime Claimsmentioning
confidence: 99%
See 1 more Smart Citation
“…The islands’ proximity to the Chinese mainland, Taiwan and Japan's southernmost islands ( nansei‐shotō ), has resulted in multiple conflicting claims that they are within all of these territories’ maritime areas, creating a complex maritime dispute. Today, Japan's position holds that the Senkaku Islands are within the 200 nautical miles that are defined as Japan's economic zone (O'Shea, , pp. 551–553) and that "there exists no issue of territorial sovereignty" (MOFA, , p. 2).…”
Section: The Senkaku Islands Dispute—territorial and Maritime Claimsmentioning
confidence: 99%
“…Vice‐Premier Deng Xiaoping reportedly suggested that it should be left to future generations to find a solution to the Senkaku Islands dispute (Fravel, , p. 157). The dispute came into focus as an IR case study again in 1992 after China specified its claims on the islands along with its maritime claims (O'Shea, , p. 551). Since that time, a series of events concerning the territory escalated the dispute to unprecedented levels.…”
Section: The Senkaku Islands Dispute—territorial and Maritime Claimsmentioning
confidence: 99%
“…Dette betyr derimot ikke at vi tar noen lands parti i denne konflikten. 2 Konflikten er både en territoriell og maritim konflikt, siden Kina og Japan har lagt fram krav om både havområdene omkring øyene i tillegg til krav om selve Senkakuøyene, se O'Shea (2015). sikkerhetspolitisk praksis: representasjonene av Kina og potensialet for militaer konflikt spilte en sentral rolle i innføringen av en begrenset versjon av kollektiv sikkerhet i 2014 og 2015.…”
Section: Innledningunclassified